ANALISIS STRUKTUR SAJIAN MUSIK IRINGAN TARI JEPIN PESAWAT TERBANG DI KOTA PONTIANAK KALIMANTAN BARAT - Kurniawan, Ya; Ismunandar, Ismunandar; Silaban, Christianly Yeli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is to structure analysis The Accompaniment music of Jepin Pesawat Terbang dance. The problem of this research, specifically, is to â€œHow is the structure of the accompaniment music of Jepin Pesawat Terbang dance? And â€œHow is the analysis description of the beruas percussion pattern of Jepin Pesawat Terbang dance accompaniment music?â€.The purpose of this research is to describe the structure of Jepin Pesawat Terbang dance accompaimet music in Pontianak City. The theory in this structure are, music analysis, background music, musicology, rhythm pattern, music form and chords.The method of this research is descriptive method analisys. The form of thisÂ research is qualitative. The approach of this research is musicology. The data of this research are from the result of interview, observation, documentation and daily notebook about background music of Jepin Pesawat Terbang dance.Â The technique of data collecting of this research are observation, direct comunication, and documentary study. Tools of data collecting in this research are the researcher as the main instrument, interview guideline, observation sheet, and documentation tool. To check the validity of this research, the researcher uses the extention of observation and the triangulation of sources. The data analysis technique are collecting the data and analyzing after the data are collected. The result of this research 1) Describe the structure of background music of Jepin Pesawat Terbang dance through music notation to every melodic instrument and percussion, 2) Analyzing The Percussion Pattern and The Beruas Instrument Of Jepin Pesawat Terbang Dance Accompaniment Music.Â Keywords : analisys, structure, musical accompaniment, Jepin Pesawat Terbang dance.